2021
DOI: 10.1021/acs.est.0c07509
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Stable Isotopes in Biota of Terrestrial and Aquatic Food Chains

Abstract: Vanadium, a potentially toxic metal, is enriched in the environment from anthropogenic releases, particularly during fossil fuel production and use and steel manufacturing. Metal stable isotopes are sophisticated tools to trace pollution; however, only recent analytical advances have allowed for the accurate and precise measurement of vanadium isotope ratios (δ51V). To examine its potential as a tracer in terrestrial and aquatic ecosystems, δ51V was measured in soil, plant, lichen, marten, and lake sediment fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
(149 reference statements)
0
17
0
Order By: Relevance
“…River sediment samples show negative δ 51 V of −0.5 to −1.7‰. 11 Schuth et al also reported δ 51 V = −0.1 to −0.76‰ for river water samples. 10 The industrially released V migrates in soils by weathering and creates −0.67 to −0.52‰ δ 51 V. 10 These isotopic variations could be explained by considering the calculated ln β for V(III) and V(IV) hydroxides (Figures 2b and 3b,c and Tables 2 and 3).…”
Section: mentioning
confidence: 93%
See 2 more Smart Citations
“…River sediment samples show negative δ 51 V of −0.5 to −1.7‰. 11 Schuth et al also reported δ 51 V = −0.1 to −0.76‰ for river water samples. 10 The industrially released V migrates in soils by weathering and creates −0.67 to −0.52‰ δ 51 V. 10 These isotopic variations could be explained by considering the calculated ln β for V(III) and V(IV) hydroxides (Figures 2b and 3b,c and Tables 2 and 3).…”
Section: mentioning
confidence: 93%
“…This may be a potential cause of the negative δ 51 V found in the aquatic food chain. 11 Since the functional groups of amino acids are categorized into O-, N-, and S-donors, 77 complexation of V with carboxylate ions may be helpful to understand the V isotope fractionation in the complexation of V with O-donor amino acids. Molecules of V(IV) oxalates are computed, and their optimized structures are shown in Figure 3o,p, and their ln β values are shown in Table 4.…”
Section: Application To Biology and Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Parallel batch tests using the same conditions as adopted in the main experiment were conducted to evaluate the bacterial viability. After the exposure of SRB to the various Ni concentrations (10,15,20,25,30, and 40 mM) at the selected time intervals (1 h, 1 day, and 1 week), 1 mL of solution was injected into a fresh Postgate B medium to assess the toxicity of Ni to the microorganisms. The SRB viability was assessed by biomass production (turbidity), and inhibition of SRB growth was assessed by relatively lower (or absent) turbidity.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Metal-stable isotope analysis has become a valuable tool in the field of environmental geochemistry with applications focusing on tracing the source and cycling of metals in the environment. …”
Section: Introductionmentioning
confidence: 99%